PERBEDAAN PENGETAHUAN, SIKAP DAN KELELAHAN PADA TINDAKAN TIDAK AMAN (UNSAFE ACTION) PEKERJA KONSTRUKSI TAHUN 2021 - Vemy Intan Amanda; Nur Aini; Erny Elviany (STIKES MITRA RIA HUSADA, 2022)
The human factor plays an important role in the incidence of work accidents based on several results. Unsafe action can be in the form of human actions that do not meet safety. Accidents can impact individuals as well as institutions. Of the global total, more than 2.78 million people die each year as a result of work-related accidents or diseases. In Indonesia, the number of work accidents shows an increasing trend, in 2017 the number of work accidents reported was 123,041 cases, meanwhile throughout 2018 it reached 173,105 cases. The purpose of this study is to know and prove the differences in knowledge, attitudes and fatigue on unsafe actions of project workers at PT X in 2021. The sample in this study amounted to 40 project workers, with quantitative research and the method used was descriptive analytic with cross sectional design and statistical test using Chi-Square with a value of = 0.05. The results showed that the percentage of workers who took unsafe actions with high risk was 26 workers (65%) and there was a significant difference in unsafe actions based on knowledge (p = 0.022), attitude (p = 0.011) and fatigue (p = 0.021). = 0.021). It is expected that the company will provide training or training to new workers and old workers, make changes to the work system such as improving work procedures that are more orderly and developing work safety programs that will be implemented in order to reduce the number of work accidents and monitor workers so that workers can comply with operational standards. prevailing in the company and increasing awareness of the importance of occupational safety and health.